Application of qPCR for multicopper oxidase gene (MCO) in biogenic amines degradation by Lactobacillus casei - Pištěková, Hana; Jančová, Petra; Berčíková, Lucie; Buňka, František; Sokolová, Iveta; Šopík, Tomáš; Maršálková, Kristýna; Amaral, Olga Maria Reis Pacheco de; Buňková, Leona (Food microbiology, 2020)
Degradation of undesirable biogenic amines (BAs) in foodstuffs by microorganisms is considered one of the most effective ways of eliminating their toxicity. In this study, we designed two sets of primers for the detection and quantification of the multicopper oxidase gene (MCO), which encodes an enzyme involved in BAs degradation, and endogenous (glyceraldehyde-3-phosphate dehydrogenase) gene (GAPDH) in Lactobacillus casei group by real-time PCR (qPCR). We tested 15 Lactobacillus strains in the screening assays (thus, MCO gene possessing assay (PCR) and monitoring of BAs degradation by HPLC-UV), in which Lactobacillus casei CCDM 198 exhibited the best degradation abilities. For this strain, we monitored the expression of the target gene (MCO) in time (qPCR), the effect of redox treatments (cysteine, ascorbic acid) on the expression of the gene, and the ability to degrade BAs not only in a modified MRS medium (MRS/2) but also in a real food sample (milk). Moreover, decarboxylase activity (ability to form BAs) of this strain was excluded. According to the results, CCDM 198 significantly (P < 0.05) reduced BAs (putrescine, histamine, tyramine, cadaverine), up to 25% decline in 48 h. The highest level of relative expression of MCO (5.21 ± 0.14) was achieved in MRS/2 media with cysteine.
Keywords: Real-Time Polymerase Chain Reaction; Oxidoreductases; Lactobacillus casei; kultivační média; Ascorbic Acid; Biogenic Amines; Gene Expression Regulation, Bacterial; regulace genové exprese u bakterií; cystein; mléko; Biogenic amines degradation; Cysteine; Lactobacillus; Primers; Chromatography, High Pressure Liquid; kyselina askorbová; Bacterial Proteins; glyceraldehyd-3-fosfátdehydrogenasy; Culture Media; Glyceraldehyde-3-Phosphate Dehydrogenases; vysokoúčinná kapalinová chromatografie; zvířata; bakteriální proteiny; Animals; biogenní aminy; kvantitativní polymerázová řetězová reakce; Milk; oxidoreduktasy; Lacticaseibacillus casei; qPCR; Histamine